The association between cigarette smoking, cancer screening, and cancer stage: a prospective study of the women’s health initiative observational cohort - Victor A Eng; Sean P David; Shufeng Li; Mina S Ally; Marcia Stefanick; Jean Y Tang (BMJ Open)
Objective To assess the dose-dependent relationship between smoking history and cancer screening rates or staging of cancer diagnoses.Design Prospective, population-based cohort study.Setting Questionnaire responses from the Women’s Health Initiative (WHI) Observational Study.Participants 89 058 postmenopausal women.Outcome measures Logistic regression models were used to assess the odds of obtaining breast, cervical, and colorectal cancer screening as stratified by smoking status. The odds of late-stage cancer diagnoses among patients with adequate vs inadequate screening as stratified by smoking status were also calculated.Results Of the 89 058 women who participated, 52.8% were never smokers, 40.8% were former smokers, and 6.37% were current smokers. Over an average of 8.8 years of follow-up, current smokers had lower odds of obtaining breast (OR 0.55; 95% CI 0.51 to 0.59), cervical (OR 0.53; 95% CI 0.47 to 0.59), and colorectal cancer (OR 0.71; 95% CI 0.66 to 0.76) screening compared with never smokers. Former smokers were more likely than never smokers to receive regular screening services. Failure to adhere to screening guidelines resulted in diagnoses at higher cancer stages among current smokers for breast cancer (OR 2.78; 95% CI 1.64 to 4.70) and colorectal cancer (OR 2.26; 95% CI 1.01 to 5.05).Conclusions Active smoking is strongly associated with decreased use of cancer screening services and more advanced cancer stage at the time of diagnosis. Clinicians should emphasise the promotion of both smoking cessation and cancer screening for this high-risk group.